Kusinang Lucban an alternative architectural historiography as a method of documentation of traditional Lucban kitchen - Correa, Katherine Anne G.
The practice of architectural heritage conservation is relatively new in the Philippines, and most documentation processes applied are based on western practices. These approaches entail understanding the significance of the site through evidence gathering methods like cultural mapping, photographic documentation, and drawing its existing state, to name a few. This study proposes an alternative historiography of architecture that can aid in understanding the significance of built heritage through the emphasis of the site and its influences. Folk narratives and sensory experiences will be considered as factors to identify the impact of a site, postulating that these accounts can be used to depict and illustrate a built heritage to become an alternative historiography documentation method.